A Rare Case of Dumbbell-shaped Primary Intraspinal Peripheral Primitive Neuroectodermal Tumor Involving Thoracic Spinal Epidural Space - Thomas, Anu Cheppanalil (Asian J Neurosurg, 2018)
Primary intraspinal primitive neuroectodermal tumor (PNET) is a type of round cell malignant tumor which is reported only above 100 in literature. We report a case of epidural thoracic peripheral PNET, discuss its pathological features, radiology, and treatment options.